Simple Photometer Development For Educational Purposes in Natural Pigment Analysis - Adhiwibawa, Marcelinus AS; Kurniawan, Jovine M (Ma Chung Research Center for Photosynthetic Pigments, 2020)
In this paper we will discuss the making of the simple photometer instrument to measure the absorbance of natural pigment crude extract. To make simple photometer, cuvette holder was printed using 3D Printing Machine, the development of simple photometer instrument also uses some components such as LED light (633 nm) as the light source, Photodiode-TSL250 as a detector and a variable resistor to set the initial intensity of light source. In this development, Arduino Uno was also used as USB data acquisition device to capture the signal from the instrument. The results of sample measurements between simple photometer instrument and UV-Vis 1800 spectrophotometer showed 98% regression coefficient of determination and simple photometer has a LOD and LOQ absorbance at 0.0267 and 0.0344. Simple photometer instrument was able to show similar response as commercial instrument. Through the development of simple photometer, student can easily understand the working principles of a spectrophotometer in natural pigment analysis that difficult to studied in detailed before.